(untitled) (International Seven Journal of Multidisciplinary, 2026)
Diabetic polyneuropathy (DPN) is the most common chronic complication of Diabetes Mellitus, affecting more than 50% of patients and severely impacting quality of life. This narrative review analyzes recent scientific evidence on the therapeutic management of DPN, ranging from pathophysiology to pain control. The pathogenesis is multifactorial, involving oxidative stress, advanced glycation, and microvascular dysfunction, which result in symmetric distal axonal damage (the “glove-and-stocking” pattern). Diagnosis remains essentially clinical, based on medical history and sensory testing using monofilaments and tuning forks. Therapeutic strategies are based on three pillars: strict metabolic control (glycemic and lipid), pathogenetic interventions (alpha-lipoic acid and benfotiamine), and management of neuropathic pain. For symptomatic relief, first-line agents such as pregabalin, duloxetine, and amitriptyline have demonstrated efficacy, with growing evidence (OPTION-DM study) supporting combination therapies for refractory cases. It is concluded that a multidimensional and individualized approach is essential to delay disease progression and reduce the risk of severe outcomes, such as ulcerations and amputations.